2013
DOI: 10.1097/ico.0b013e31825d586b
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Donor Cornea Contamination

Abstract: Although the genesis of donor cornea contamination seems to be multifactorial, resident species from physiological skin flora are the main contaminants indicating that the donor corpses could be the main source of microbiological contamination. A change in the explantation technique was followed by an increase in the contamination rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 21 publications
1
9
1
Order By: Relevance
“…It is a severe complication of intraocular surgeries like penetrating keratoplasty (PK) or cataract surgery where the risk of bacterial or fungal infection increases with transplantation of a contaminated cornea [1, 2]. It has been shown that the microorganisms responsible for the postoperative endophthalmitis are usually derived from the transplanted corneas; however, involvement of other postoperative risk factors for ocular infection has also been determined [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is a severe complication of intraocular surgeries like penetrating keratoplasty (PK) or cataract surgery where the risk of bacterial or fungal infection increases with transplantation of a contaminated cornea [1, 2]. It has been shown that the microorganisms responsible for the postoperative endophthalmitis are usually derived from the transplanted corneas; however, involvement of other postoperative risk factors for ocular infection has also been determined [3].…”
Section: Introductionmentioning
confidence: 99%
“…These differences are possibly due to variation in mean time before tissue collection. The study by Linke et al (2013) had a mean time to collection of 40 hours and found an association with contamination, while the Khouani et al (2014) had a much shorter mean time to collection (9.7 hours) and found no association with contamination. Instances of drowning may lead to longer time before tissue collection than hospital deaths, but the approximate added mean time of submersion (prior to the victim being pronounced deceased) for our sample was 38 min, and thereby likely minimal enough to not affect corneal contamination.…”
Section: Discussionmentioning
confidence: 82%
“…This practice has been debated because controversial evidence surrounding the risks to the transplant recipient. A study by Linke et al (2013), of the Hamburg eye bank, suggests that longer death-to-procurement times are associated with greater corneal contamination, possibly due to transfer of flora from skin and environment. However, a study by Khouani et al (2014) found no association between these factors.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Another report showed that the median annual contamination rate was 5.3%. 14 In fact, it has been reported that Candida albicans is responsible for the majority of fungal infections post PKP and Descemet's stripping automated endothelial keratoplasty. 3 , 4 , 5 , 6 , 7 , 9 , 15 , 16 …”
Section: Discussionmentioning
confidence: 99%